WALTZ ONLINE WITH NUKES: : TOWARDS A DEFINITION OF “STRATEGIC” IN 21ST -CENTURY INTERNATIONAL POLITICS (Hoplos - Revista de Estudos Estratégicos e Relações Internacionais, 2025)
The thought of Kenneth Waltz has been the focus of attention in International Relations theory in the last four decades at least. Recently, Waltz’s thought has been revisited in a number of ways.This paper aims at revisiting his work understanding his definition of threat, and who/what is the subject and the object of a threat in the international system. I turn to applying such a discussion to two realms of contemporary interest: that of nuclear weapons, about which Waltz discussed very lengthy; and to that of cybersecurity, which Waltz wrote nothing about. Understanding how force is used in each of these realms, I propose a reflection on the concept of “strategic” and how it can be derived from Waltz’s theoretical thought.